2021
DOI: 10.1007/s13337-021-00662-x
|View full text |Cite
|
Sign up to set email alerts
|

First report of Cucumber mosaic virus infecting Ocimum gratissimum (L.) in Calabar, Cross River State, Nigeria

Abstract: Leaf samples of Ocimum gratissimum (L.) exhibiting vein banding, mosaic and chlorotic spots were collected randomly from the field. The symptomatic samples reacted positively to specific CMV antibody in antigen coated plate enzyme linked immunosorbent assay and to confirm the presence of CMV, RT-PCR was performed using CMV-specific primers that amplify a 519 bp region from the viral coat protein gene. The expected amplicon shared homology of 97.06% with a Nigerian isolate MH178110. Phylogenetic tree constructe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
1
2
0
Order By: Relevance
“…However, they were clustered to the IB subgroup. Previously characterised CMV isolates, especially from Nigeria, have been placed in either subgroups IA, IB or II (Ayo-John and Hughes, 2014; Kayode et al, 2014;Ekpiken et al, 2021). The occurrence of subgroup IB in this study, and its prevalence in Nigeria, strongly supports an earlier report by Haase et al (1989) which suggested that subgroup I isolates were more commonly found in the tropics and subtropics while subgroup II isolates were prevalent in the temperate regions.…”
Section: Analysis Of Sequencessupporting
confidence: 84%
See 1 more Smart Citation
“…However, they were clustered to the IB subgroup. Previously characterised CMV isolates, especially from Nigeria, have been placed in either subgroups IA, IB or II (Ayo-John and Hughes, 2014; Kayode et al, 2014;Ekpiken et al, 2021). The occurrence of subgroup IB in this study, and its prevalence in Nigeria, strongly supports an earlier report by Haase et al (1989) which suggested that subgroup I isolates were more commonly found in the tropics and subtropics while subgroup II isolates were prevalent in the temperate regions.…”
Section: Analysis Of Sequencessupporting
confidence: 84%
“…Table 1 and Figure 4 showed that the 31 isolates, including those retrieved from GenBank, were divided into four main phylogroups inconsistent with geographic origins and hosts, with each phylogroup sub- (Adediji, 2019;Arogundade et al, 2019;Eyong et al, 2020;Ekpiken et al, 2021;Apalowo et al, 2022;Longe et al, 2022). The present investigation revealed the natural occurrence of CMV on P. foetida with its detection and identification based on ELISA testing and sequencing of its partial genome.…”
Section: Analysis Of Sequencesmentioning
confidence: 99%
“…For example, CMV infects plant species belonging to different botanical families, such as Brassicaceae , Solanaceae , Papilionaceae , and Cucurbitaceae , including weeds and ornamental plants such as Chenopodium amaranticolor , Datura innoxia , Hibiscus rosa or Salvia splendens [ 49 , 50 , 51 ]. Recently, it has also been reported to infect Ocimum gratissimum L. in Nigeria [ 52 ] and Tylophora indica in India [ 53 ]. In Spain, CMV has been found to be widely distributed in cucumber, melon, pumpkin, zucchini, watermelon, tomato, pepper, aubergine, tobacco, beans, celery, and borage horticultural crops, among others [ 42 , 47 , 50 , 54 ].…”
Section: Description Of the Main Aphid-transmitted Virus In Cucurbitsmentioning
confidence: 99%